Investigations of the g factors and local structure for orthorhombic Cu²+(1) site in fresh PrBa₂Cu₃O₆+x powders - Kuang, M.Q.; Wu, S.Y.; Song, B.T.; Hu, X.F. (Condensed Matter Physics, 2012)
The electron paramagnetic resonance (EPR) g factors gx, gy and gz of the orthorhombic Cu²⁺ (1) site in fresh PrBa₂Cu₃O₆+x powders are theoretically investigated using the perturbation formulas of the g factors for a 3d⁹ ion under orthorhombically elongated octahedra. The local orthorhombic distortion around the Cu²⁺(1) site due to the Jahn-Teller effect is described by the orthorhombic field parameters from the superposition model. The [CuO6]¹⁰⁻ complex is found to experience an axial elongation of about 0.04 Å along c axis and the relative bond length variation of about 0.09 Å along a and b axes of the Jahn-Teller nature. The theoretical results of the g factors based on the above local structure are in reasonable agreement with the experimental data.